2009
DOI: 10.1007/s11274-009-0237-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al and heavy metals on enzymes of nitrogen metabolism of fast and slow growing rhizobia under explanta conditions

Abstract: Most of the legume crops are affected by metal stress present in the soil mainly due to contaminated agrochemicals and sewage sludge. The effect of aluminium, and heavy metals copper, iron and molybdenum on growth and activity of enzymes of fast and slow growing rhizobial sps. was studied. Sinorhizobium meliloti RMP 5 was found to be more tolerant to metal stress than Bradyrhizobium BMP 1 . Both the strains were extremely sensitive to Al than other metals. Al was much more deleterious for the enzymatic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 28 publications
2
26
0
2
Order By: Relevance
“…In comparison to E. meliloti RMP 6 , Bradyrhizobium BMP7 Tet+Kan+ showed better PGP and symbiotic potential. Similar results were reported in earlier studies by Arora et al (2000Arora et al ( , 2010. Production of ACC deaminase by RMP6 Ery+Kan+ may contribute to the nodulation ability.…”
Section: Discussionsupporting
confidence: 92%
“…In comparison to E. meliloti RMP 6 , Bradyrhizobium BMP7 Tet+Kan+ showed better PGP and symbiotic potential. Similar results were reported in earlier studies by Arora et al (2000Arora et al ( , 2010. Production of ACC deaminase by RMP6 Ery+Kan+ may contribute to the nodulation ability.…”
Section: Discussionsupporting
confidence: 92%
“…Nitrogenase activity in the cells was, however, reduced significantly in the presence of the dyes and metals with just 15 to 25 % activity of that in the control (4.46 nmol C 2 H 4 h −1 mg −1 dry wt). A sharp reduction in nitrogenase in differently growing rhizobia has also been reported by Arora et al (2010) in the presence of heavy metals. Increased hydrogenase activity and downregulated nitrogenase activity in the presence of metals/dyes need to be investigated in detail to understand the mechanism of their action.…”
Section: Tolerance Studiessupporting
confidence: 62%
“…Apart from the effects of heavy metals on plants, numerous studies have also shown that long-term accumulation of heavy metal in soils deleteriously affects community diversity including those of denitrifying community (Sobolev and Begonia 2008) or soil microbial activities (Doelman and Haanstra 1984;Hemida et al 1997;Solanki and Dhankhar 2011) including those of hydrogenase activity of Rhizobium leguminosarum biovar viciae (Ureta et al 2005). For example, in a study, the impact of aluminum and heavy metals such as copper, iron, and molybdenum on growth and activity of enzymes of fast-and slow-growing rhizobial species was determined (Arora et al 2010). Of these, copper had inhibitory effect on growth and enzyme activities of Bradyrhizobium strain at all concentrations.…”
mentioning
confidence: 99%